Antiviral Effects of Alpinone on Atlantic Salmon (Salmo Salar) Infected with the Infectious Pancreatic Necrosis Virus - Imarai-Bahamonde, C; Modak-Canobra, B (Elsevier Ltd, 2025)
Infectious pancreatic necrosis virus (IPNV) poses a significant threat to the aquaculture industry, primarily affecting juvenile salmonids, which often experience high mortality rates. Several therapies are being developed to control infections in fish, such as vaccines and immunostimulants; however, antiviral therapies are scarce and have limited effectiveness. Therefore, the search for compounds that can enhance antiviral responses is crucial for the sustainable growth of aquaculture. This study aimed to contribute to the search for new therapeutic agents to control Infectious Pancreatic Necrosis Virus (IPNV) by evaluating the antiviral effects of Alpinone in an experimental infection in Atlantic salmon (Salmo salar). A total of ninety fish, each weighing approximately 15 grams, were randomly selected and divided into three groups. The fish were intramuscularly injected with one of the following treatments: (i) 50 μg of Alpinone in saline (n=30), (ii) a 3% Montanide solution (n=30), or (iii) a saline solution (n=30). On day 30, all fish received an intraperitoneal injection of the IPNV (VR-299 strain). On day 30, all fish received an intraperitoneal injection of IPNV (VR-299 strain). After euthanizing the fish, head kidneys and gills, the latter a mucosal tissue that in natural infections serves as the initial point of contact with microorganisms, were collected for analysis on days 0, 5, and 26 post-infection. Signs associated with the infection were recorded on day 5 post-infection. The analysis showed that Atlantic salmon treated with Alpinone 30 days before IPNV infection exhibited fewer clinical signs of the disease and a reduction in viral load by three orders of magnitude compared to both Montanide-treated and untreated fish. The gene expression of immune response indicators, including ifn-γ, il-8, il-12β, tgf-β, and mx, was analyzed in the gills using real-time PCR. The results showed that the expression of il-8 and il-12β increased on day 5 after IPNV infection solely in the Alpinone-treated fish, which may be related to the lower viral loads and fewer clinical signs present in this group. Overall, this study demonstrated that Alpinone has a significant antiviral effect on IPNV infection in Atlantic salmon, which correlates with elevated levels of genes encoding IL-8 and IL-12, two pro-inflammatory and immunomodulatory cytokines that enhance the host s defense mechanisms in fish. © 2025